Coexistence et confrontation des modèles agricoles et alimentaires - Gasselin, Pierre; Lardon, Sylvie; Cerdan, Claire; Loudiyi, Salma; Sautier, Denis (éditions Quae, 2021)
New agricultural and food models are being deployed in the territories in response to criticism of old forms and to face new challenges. They embody archetypes of the diversity observed, actor projects or even new standards. The authors here analyze situations of coexistence and confrontation of agricultural and food models according to four major dimensions of territorial development: the tension between specialization and diversification, innovation, adaptation and food transition. A series of conceptual works and case studies in France and around the world make it possible to understand the interactions between these models (confrontation, complementarity, coevolution, hybridization, etc.), beyond the characterization of their diversity and of evaluation of their relative performance. The coexistence and confrontation of these models strengthen their capacity for radical change. The book highlights the original questions of the analytical framework, its methodological challenges and the expected consequences for supporting agricultural and food development in rural and urban areas. It is intended for researchers, teachers, students and professionals interested in territorial development.